Psychiatric aspect of most common used cardiological drugs - Cholewa, Krystian; Wysokińska, Olga; Siwek, Michał; Kozyra, Magdalena; Rudziński, Gracjan; Milanowska, Joanna (Journal of Education, Health and Sport, 2020)
Introduction: The count of psychiatric patients is growing. The same trend it is observed among cardiovascular diseases and metabolic like diabetes. Many people take drugs which may affect on mental state. On the one hand that drugs could have pleotropic mechanism of action which are beginning to use in treatment of psychiatry. The other hand is showed undiscovered field of impact on brain working. Methods and Aim: Shown the psychiatric aspect, like side effects and unusual use, of the most used cardiological drugs. To do this, research of articles was done with the help of deta bases such as PubMed and Google Scholar. Results: The most used cardiological drugs are beta blockers, calcium canal blockers, ACE inhibtors, ARBs, nitrats, cilostazol, amiodarone and clonidine In this article it was shown current known about those drugs like mechanism of action and a report of psychiatric clinical trials. Beta-blockers are the most commonly used group of cardiological drugs as the one that significantly affects mental health. Their therapeutic importance has been noted in diseases such as: PTSD or stage fright. It was also long believed that they could make depression worse, but the latest research strongly contradicts this. A positive effect in the treatment of depression can also be obtained by usage of inhibitors of the RAA. Calcium channel blockers are another group of cardiac drugs that are important in the regulation of mood in bipolar disorder. To sum up, a large proportion of cardiac drugs can influence the flow of psychiatric diseases, and the use of them may be clinically desirable in patients with both - cardiac and psychiatric problems.